2002
DOI: 10.1152/ajpendo.2002.282.1.e11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute exercise on uncoupling protein 3 is a fat metabolism-mediated effect

Abstract: Human and rodent uncoupling protein (UCP)3 mRNA is upregulated after acute exercise. Moreover, exercise increases plasma levels of free fatty acid (FFA), which are also known to upregulate UCP3. We investigated whether the upregulation of UCP3 after exercise is an effect of exercise per se or an effect of FFA levels or substrate oxidation. Seven healthy untrained men [age: 22.7 +/- 0.6 yr; body mass index: 23.8 +/- 1.0 kg/m(2); maximal O2 uptake (VO2 max): 3,852 +/- 211 ml/min] exercised at 50% VO2 max for 2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
75
5
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 37 publications
2
75
5
5
Order By: Relevance
“…Our results provide evidence that exercise does not result in major changes in the ratio of UCP3 to other mitochondrial constituents. This is in contrast to the picture provided by previous studies of marked alterations in mitochondrial composition, with an initial large disproportional increase in UCP3 with one exercise bout (33,37) and a large decrease in UCP3 with training (6,29).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results provide evidence that exercise does not result in major changes in the ratio of UCP3 to other mitochondrial constituents. This is in contrast to the picture provided by previous studies of marked alterations in mitochondrial composition, with an initial large disproportional increase in UCP3 with one exercise bout (33,37) and a large decrease in UCP3 with training (6,29).…”
Section: Discussioncontrasting
confidence: 99%
“…recovery." Similarly, Schrauwen et al (29) reported that UCP3 expression was significantly lower in muscles of trained compared with untrained men and that maximal oxygen uptake capacity was negatively correlated with UCP3. In these studies, UCP3 mRNA, rather than actual UCP3 expression, was measured.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations